UJI SUBSTANTIF PASAL 212 KHI DALAM SENGKETA PENARIKAN HIBAH: STUDI KOMPARATIF DUA PUTUSAN PERADILAN AGAMA - Mohamad Sar'an; Sahril Sidik; Ramdani Wahyu Sururie (Universitas Nurul Jadid, 2026)
This study examines the dialectics of judicial reasoning (rechtsvinding) in disputes over the revocation of gifts (ruju’ fi al-hibah) through the lens of the abuse of rights doctrine (ta’assuf fi isti’mal al-haq). Historically, Article 212 of the Compilation of Islamic Law (KHI) is often misunderstood as a norm granting absolute authority to parents to revoke a gift, rendering it devoid of material boundaries and potentially triggering injustice. Through normative legal research employing conceptual and comparative approaches to the Surabaya Religious Court Decision No. 5001/Pdt.G/2018/PA.Sby and Supreme Court Decision No. 467/K/AG/2017, this article reveals that the judiciary has shifted towards substantive justice. Judicial disparity occurs not due to inconsistent textual adherence, but as a manifestation of the judge's acuity in detecting bad faith. The Surabaya Religious Court canceled a gift to punish manipulation and defect of will (wilsgebreke) by the child, while the Supreme Court canceled a gift to prevent the exploitation of marital property by the parent without spousal consent. As a core finding, this article deconstructs the right of revocation into a